Rotor-Dynamic Characteristic Evaluation of Interior Permanent Magnet Motor using Finite Element Method - Hilman Syaeful Alam; Pudji Irasari (Journal of Mechatronics, Electrical Power and Vehicular Technology, 2014)
Dynamic characteristics of a critical speed of the rotor components at interior permanent magnet motor were evaluated using one-dimensional (1D) and three-dimensional (3D) finite element methods. Critical speed of the rotor wasinvestigated in the Campbell diagram, which shows the relationship between natural frequency and rotational velocity of the system when the motor is not in operation. The 1D finite element analysis shows that there are two modes which are close to the design frequency of 300 Hz i.e. mode 1 and 2. However the critical rotational velocity in both modes are still far above the maximum velocity design of 6,000 rpm. Validation using 3D finite element analysis demonstrated that all modes were still above the designed frequency and did not find any critical speed below 6,000 rpm. It can be concluded that the critical speed of the rotor of IPM motor is still outside the system resonance region, and can be operated safely.